Pengembangan Pulo Tareba Sebagai Destinasi Ekowisata - Limpas, Zulhajnie Wildayanti (SENTRI: Jurnal Riset Ilmiah, 2025)
This paper discusses the development of a new tourist destination on Ternate Island, namely Pulo Tareba Ecotourism, which is managed directly by the local community as a form of community-based tourism. The study aims to analyze the existing facilities, identify aspects that have been developed, and determine areas that still require improvement to enhance tourism quality and visitor satisfaction. Using qualitative descriptive methods with observation and interview techniques, primary data were obtained through direct observation at the Pulo Tareba site and interviews with ecotourism managers and community members, while secondary data were gathered from literature studies, government documents, and related news articles. The results show that Pulo Tareba Ecotourism still needs improvement in several key aspects, including infrastructure, safety, and supporting facilities. In addition, accessibility, waste management, and promotional strategies must be strengthened to increase tourist visits. Collaboration between the local community, government, and private sector is essential to ensure sustainable tourism development, strengthen the economic potential of the area, and position Pulo Tareba as a new tourism icon that reflects the natural beauty and cultural richness of Ternate Island.